Pengaruh Penyuluhan terhadap Sikap Ibu Menangani Febris Pasca Imunisasi DPT - Lia Rahmawati; Wahyu Wibisono (STIKes Patria Husada Blitar, 2014)
DPT is an attempt to get immunity against the disease Diphtheria, Pertussis , Tetanus by entering the germs of diphtheria , pertussis , tetanus that have beenweakened and turned off into the body so that the body can produce antibodies that will be used for the the body to fight the germs or the three of the disease ( Markum , 2005). The aim of this study was to determine the effectiveness health promotion to the mother’s attitudes post DPT immunization on the 3-5 months infants. Method: Research design was Pre-Experimental design using Pre - Post Test approach. Research sample was 19 mothers with infants aged 3-5 months at Pustu slorok District of Garum at June 25 until June 27th th ,2012, its choosed with total sampling. Data collected by questionaire. Analysis using Wilcoxon Sign Rank Test, with ≤0.05 significant level. Result: The results showed that there was an effect of health promotion to the mother’s attitudes in handling in febrile post DPT , with p value of 0.046. Discussion: Based on the results of the research,it was expected for the respondents to be more active in improving knowledge by emphasizing on information about febrile post DPT immunization either electronic nor mass media so respondents could improve the attitude in handling the febrile post DPT and minimize the occurrence of Kipi ( Genesis Infection Post Immunization ).